2005
DOI: 10.1042/bst0330119
|View full text |Cite
|
Sign up to set email alerts
|

1994–2004: 10 years of research on the anaerobic oxidation of ammonium

Abstract: The obligately anaerobic ammonium oxidation (anammox) reaction with nitrite as primary electron acceptor is catalysed by the planctomycete-like bacteria Brocadia anammoxidans, Kuenenia stuttgartiensis and Scalindua sorokinii. The anammox bacteria use a complex reaction mechanism involving hydrazine as an intermediate. They have a unique prokaryotic organelle, the anammoxosome, surrounded by ladderane lipids, which exclusively contains the hydrazine oxidoreductase as the major protein to combine nitrite and amm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(83 citation statements)
references
References 44 publications
2
79
0
1
Order By: Relevance
“…By 2010, Bae et al [30] using PCR (polymerase chain reaction) methods identified six anammox genera in activated sludges taken from WWTPs; three freshwater, two marine environment and one mixed species are also generally acknowledged. With discovery of more species and habitats, we anticipate that more versatile species will be identified, but their overall diversity remains relatively unknown [31]. Though surprisingly widespread, anammox bacteria discovered within each ecosystem appear to be dominated by a single anammox genus, indicating specialization for distinct ecological niches [32].…”
Section: Anammox and Wastewater Treatmentmentioning
confidence: 99%
“…By 2010, Bae et al [30] using PCR (polymerase chain reaction) methods identified six anammox genera in activated sludges taken from WWTPs; three freshwater, two marine environment and one mixed species are also generally acknowledged. With discovery of more species and habitats, we anticipate that more versatile species will be identified, but their overall diversity remains relatively unknown [31]. Though surprisingly widespread, anammox bacteria discovered within each ecosystem appear to be dominated by a single anammox genus, indicating specialization for distinct ecological niches [32].…”
Section: Anammox and Wastewater Treatmentmentioning
confidence: 99%
“…The anammox process is biochemically distinct from denitrification, as it involves hydrazine as an intermediate and forms N 2 by a one-to-one combination of nitrogen from the two sources (van de Graaf et al 1995; Strous et al 1999;Jetten et al 2005). In contrast, denitrification, used here in the strict or canonical sense, is a stepwise enzymatic reduction of nitrate via nitrite, nitric oxide, and nitrous oxide to N 2 (Zumft 1997;Codispoti et al 2001).…”
mentioning
confidence: 99%
“…However, sediment anoxia may lead to the reduction of NO 3 -and nitrite (NO 2 -) to N 2 (or N 2 O) by denitrification (Rissanen et al 2011). Recently, ''anaerobic ammonium oxidation'' (anammox) has been identified as another process of N 2 release under anoxic conditions (Jetten et al 2005).…”
Section: Cascading Influences From Terrestrial Watersheds To Estuariesmentioning
confidence: 99%